2002
DOI: 10.1159/000083117
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia in the Elderly: A Comparison of Benign Etiologies of Hoarseness in Two Different Cultures

Abstract: Objective: The objective of this study was to review the benign causes of hoarseness in the elderly above 60 years of age and to compare them between the two different cultures of Switzerland and Turkey. Material and Method: 140 patients were enrolled in the study, 69 (37 males, 32 females; mean age 66 years) from Berne, Switzerland, and 71 (41 males, 30 females; mean age 63 years) from Izmir, Turkey. Results and Conclusions: In the Berne study group, the most common benign causes of hoarseness registered in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Both hoarseness and the RSST score as outcome measurements were significantly improved after intervention. Since hoarseness causes vocal fold bowing [41], functional dysphonia [42], or unilateral vocal fold paralysis among elderly people [41,42], the abovementioned result showed a recovery of vocal cord physical status or function. Furthermore, the RSST test is consisted of the oral function, the pharyngeal function and the coordination between swallowing and respiration.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Both hoarseness and the RSST score as outcome measurements were significantly improved after intervention. Since hoarseness causes vocal fold bowing [41], functional dysphonia [42], or unilateral vocal fold paralysis among elderly people [41,42], the abovementioned result showed a recovery of vocal cord physical status or function. Furthermore, the RSST test is consisted of the oral function, the pharyngeal function and the coordination between swallowing and respiration.…”
Section: Discussionmentioning
confidence: 95%
“…We selected a pushing exercise with the simultaneous voice and a falsetto [i:] as new exercise intervention, especially focusing on the pharyngeal stage in the 5 swallowing stages. A pushing exercise and a falsetto [i:] lead to strengthen the closure force of the vocal cords and the movement of the larynx to prevent aspiration [19,41,42]. To assess symptom improvement after intervention, voice clarity and swallowing function tests were observed [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic suppurative otitis media (CSOM) was the most common infectious disease, affecting 28 (8.8%) patients whereas presbyacusis was identified in 20 (6.3%) of the patients. Kandogen and Seifert (2002) conducted similar studies in their respective countries, Turkey and Switzerland which was published together. Their studies conducted between these two cultures revealed that laryngopharyngeal conditions were prominent in the old aged.…”
Section: Opoku-buabeng 19mentioning
confidence: 96%